Władysław Dziadoń, the Kraków 'King of Shoes'. (March 2019) - Kowalska, Joanna Regina
Abstract : The Kraków shoemaker Władysław Dziadoń was called the king of shoes among citizens of Kraków. He worked in shoemaking between the years 1920 and 1955. His dream was to create a company of comparable significance to the Czechoslovakian Bata shoe company. During the years of the German occupation in the Second World War, he provided support to the resistance movement, without giving up the business of producing shoes. While he was hopeful that after the war he would be able to realize his dreams and aspirations, the conditions of a totalitarian state and the communist economy meant that these plans were never able to materialize. He was persecuted by the communist state, and in 1955 he had to close his shoe company. In the collections of the National Museum in Kraków there are thirty pairs of shoes made by his company, another three pairs are preserved in a private collection. This high-quality footwear is the only material legacy of Władysław Dziadoń's skills as a producer of shoes. This article illustrates the fate of a shoemaker and entrepreneur in the era of the German occupation (1939–1945) and Stalinism (1945–1955).